(untitled) (Modern education and development, 2025)
This article is devoted to the topic “Financial markets and issues of improvement of their activities” and analyzes the main functions, structure of financial markets and their place in the economy. The article examines ways to improve the efficiency of financial markets, ensure security for investors and consumers, as well as improve market performance by introducing financial innovation. The article also covers changes in global financial markets, digital transformation, and the impact of fintech technologies. The legislative and regulatory mechanisms necessary to ensure the stability of financial markets are analyzed, as well as international experiences.